2011
DOI: 10.1111/j.1439-0434.2011.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil‐applied Zinc and Manganese on the Development of Rhizoctonia Aerial Blight of Soybean

Abstract: Ivanete vanete Tonole onole Silva ilva, Fabrıcio abrício Á vila vila Rodrigues odrigues and Julio ú lio Cezar ezar Parpaiola arpaiola Baroni aroni Abstract This study aimed to investigate the effect of soilapplied zinc (Zn) and manganese (Mn) rates on the development of aerial blight, caused by Rhizoctonia solani Ku¨hn, in soybean. Plants (cv. ÔConquistaÕ) were grown in a typical Acrustox red-yellow latosol amended with Zn rates (applied as ZnSO 4AE 7H 2 O; 24% Zn) of 0, 1, 2, 4, 8 and 16 mg⁄dm 3 of soil and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In contrast to the results found with soybean rust, leaflets from plants in the –Zn treatment had higher populations of aphids, higher numbers of wounds infected with bacterial pustule, and larger areas of necrosis caused by S. sclerotiorum compared with the physiologically optimal Zn treatment. Similar contrasting results between pathogens in other host‐pathogen systems from field and soil pot trials have been reported ( Deb and Dutta , 1992; Latha et al, 1997; Silva et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In contrast to the results found with soybean rust, leaflets from plants in the –Zn treatment had higher populations of aphids, higher numbers of wounds infected with bacterial pustule, and larger areas of necrosis caused by S. sclerotiorum compared with the physiologically optimal Zn treatment. Similar contrasting results between pathogens in other host‐pathogen systems from field and soil pot trials have been reported ( Deb and Dutta , 1992; Latha et al, 1997; Silva et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…This result is consistent with the results found in an earlier study of the effects of nutrients on sugar cane rust severity, which reported a similar relationship with rust severity increasing as Zn concentration increased ( Anderson and Dean , 1986). Soybean rust and aerial blight, found to increase in severity with increasing Zn, belong to the same class of fungi—the Basidiomycetes ( Silva et al, 2012). However, drawing general conclusions on the relationship between Zn nutrition and fungal pathogen classification will require further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al. () also found that the resistance of soybean plants to aerial blight, caused by R. solani , was not affected by the soil‐applied Zn rates ranging from 0 to 16 mg/dm 3 of soil. It is plausible that the greater susceptibility of rice plants against B. oryzae infection as the Zn concentrations in leaf tissues increased can be associated with the stimulation for production of non‐selective toxins that become deleterious to the leaves.…”
Section: Resultsmentioning
confidence: 96%
“…Accordingly, Zn supplied as a soil drench increased the severity of powdery mildew in wheat through a combination of pathogen stimulation and host predisposition (Meyer 1950). The severity of aerial blight caused by R. solani in the leaves of soybean plants was greater as the Zn rates increased in the soil (Silva et al 2012). Zinc can improve mycelial growth of several fungi species by increasing nitrogen uptake (Duffy 2007), therefore enhancing pathogen's aggressiveness.…”
Section: Sources Of Variationmentioning
confidence: 99%